Exploring the Performance and Challenges of AC and DC Coupled Solar Hybrid Systems in Malaysian Rural Schools - Arifin, Azlan; Mohamed, Ramizi; Muhaimin Mahmud, Abdul (European Journal of Sustainable Development, 2025)
Reliable energy access in rural schools is necessary for educational and community development. Solar hybrid systems, particularly Direct Current (DC) Coupled designs, offer a sustainable solution. However, they face significant scalability, maintenance complexity, and charge controller dependency challenges. This paper addresses these issues and presents an adaptive model to optimize DC Coupled solar hybrid systems. Applying Basic Qualitative Inquiry, semi-structured interviews were conducted during this study with five experts, including site officers, maintenance contractors, and a senior electrical engineer. The results reveal that rigid system design, high upgrading costs, and charge controller inefficiencies limit scalability and long-term performance. System reliability will suffer from a lack of maintenance, especially battery management and overheating prevention. The Adaptive DC Coupled System Solution Model (ADCSM) was proposed to overcome these challenges, including adaptive system restructuring, AC-DC hybrid integration, advanced charge controller optimization technologies, and intelligent monitoring technologies. This paradigm improves the system’s flexibility, efficiency, and sustainability and provides a cost-effective and scalable strategy for policymakers, engineers, and researchers to manage rural energy. Keywords: Solar Hybrid Systems, DC Coupled, Scalability Challenges, Charge Controller Optimization, Renewable Energy in Rural Schools.